2017
DOI: 10.1111/syen.12276
|View full text |Cite
|
Sign up to set email alerts
|

Morphological variation, genetic differentiation and phylogeography of the East Asia cicada Hyalessa maculaticollis (Hemiptera: Cicadidae)

Abstract: The cicada Hyalessa maculaticollis is widely distributed in East Asia, and is noted for its great morphological variability. The variation in this species and its allies has been a long-standing controversy. The population differentiation, genetic structure and phylogeography of this species are explored based on morphological observations, mitochondrial and nuclear DNA analyses, and comparison of the calling song structure of males. Our results reveal that the abundant intraspecific morphological variations a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 70 publications
5
16
0
Order By: Relevance
“…Our data substantiate the possibility that the ECS land bridge may have served as a “dispersal corridor” for East Asian insects and connected Mainland China, the Korean Peninsula, and Southern Japan [33,34,35]. This hypothesis has also been supported by the results of studies on hemipterans [16,25]. Since their climates were unfavorable, however, South Korea and Japan may have restricted their populations to relatively narrow distributions.…”
Section: Discussionsupporting
confidence: 83%
“…Our data substantiate the possibility that the ECS land bridge may have served as a “dispersal corridor” for East Asian insects and connected Mainland China, the Korean Peninsula, and Southern Japan [33,34,35]. This hypothesis has also been supported by the results of studies on hemipterans [16,25]. Since their climates were unfavorable, however, South Korea and Japan may have restricted their populations to relatively narrow distributions.…”
Section: Discussionsupporting
confidence: 83%
“…COI sequences have been proposed as an effective barcoding tool for animal identification [47,48,49] and have been successfully used for the identification of cicadas [46,50]. We found that COI sequences enabled accurate classification at the species level.…”
Section: Discussionmentioning
confidence: 85%
“…Geographic isolation is essential to most speciation events, because biogeographic barriers (due to distance, water bodies, mountains, deserts, etc.) separate populations, impede gene flow, and drive genetic differentiation, which may lead to allopatric speciation [13]. The mosaic of high mountains in East Asia forms a complex terrain imposing geographical barriers hindering movement of many animal species [1, 4].…”
Section: Introductionmentioning
confidence: 99%
“…separate populations, impede gene flow, and drive genetic differentiation, which may lead to allopatric speciation [13]. The mosaic of high mountains in East Asia forms a complex terrain imposing geographical barriers hindering movement of many animal species [1, 4]. The uplift of the Qinghai-Tibet Plateau (about 1.7–3.6 million years ago (Ma)), in particular, had a profound impact on the surrounding geography and environment, generating sources and reservoirs of genetic and species diversity [5, 6].…”
Section: Introductionmentioning
confidence: 99%